2009
DOI: 10.1152/ajpheart.01320.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous calcium release in tissue from the failing canine heart

Abstract: malities in calcium handling have been implicated as a significant source of electrical instability in heart failure (HF). While these abnormalities have been investigated extensively in isolated myocytes, how they manifest at the tissue level and trigger arrhythmias is not clear. We hypothesize that in HF, triggered activity (TA) is due to spontaneous calcium release from the sarcoplasmic reticulum that occurs in an aggregate of myocardial cells (an SRC) and that peak SCR amplitude is what determines whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 43 publications
(45 reference statements)
3
48
0
1
Order By: Relevance
“…The mSCR rise time was defined as the time between the minimal fluorescence after the last paced beat, to the peak fluorescence of the mSCRs. The slope of mSCRs, a determinant of triggered activity, 31 was calculated by dividing mSCR amplitude by mSCR rise time. In any given experiment, under every condition, the 10 sites with the largest mSCR amplitude were analyzed for mSCR and DAD parameters; average data of these sites is presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mSCR rise time was defined as the time between the minimal fluorescence after the last paced beat, to the peak fluorescence of the mSCRs. The slope of mSCRs, a determinant of triggered activity, 31 was calculated by dividing mSCR amplitude by mSCR rise time. In any given experiment, under every condition, the 10 sites with the largest mSCR amplitude were analyzed for mSCR and DAD parameters; average data of these sites is presented.…”
Section: Discussionmentioning
confidence: 99%
“…This is manifest in the biphasic nature of the mSCR slope and DAD amplitude (Figure 2B), both of which are directly related to triggered activity occurrence. 31 In other words, slow RyR release kinetics is the predominant effect during TH, resulting in decreased mSCR slope and DAD amplitude. However, RyR-Po increases exponentially with decreasing temperature, which would make it much more predominant at SH, relative to RyR conductance.…”
Section: Mechanisms Underlying the Temperature-dependent Effects Of Hmentioning
confidence: 99%
“…This mechanism forms the basis for the typical rate and magnitude dependence of DADs: the faster is the triggering rhythm, the shorter is the interval of the triggered response and the faster are self-sustaining trains of DADs (Katra & Laurita, 2005). In other words, only spontaneous SR Ca 2+ release events of sufficient magnitude and rate occurring at multiple sites synchronously within the cell will trigger DAD-mediated action potentials (Hoeker et al, 2009). The action potential initiation from a DAD is facilitated in cardiac myocytes from failing hearts, because of the increased expression of NCX and the reduction of repolarizing K + currents as a consequence of the electrophysiological remodelling (Tomaselli & Zipes, 2004).…”
Section: Role Of Ca 2+ In Dadsmentioning
confidence: 99%
“…Simplified electrophysiological mechanism underlying delayed afterdepolarization and triggered activity: spontaneous SR Ca 2+ release ("Ca 2+ leak") through dysfunctional RyR2 activates NCX exchange and causes membrane positive oscillations (DADs), which may escalate into triggered action potentials and sustained triggered activity (adapted from Kockskamper & Pieske, 2006). (Hoeker et al, 2009;Mulder et al, 1989), the mechanisms underlying triggered activity in situ remain elusive. It is unknown whether spontaneous Ca 2+ oscillations originate from the extracellular space through L-type Ca 2+ channels, or from SR via RyR2, or perhaps from other sources (e.g.…”
Section: Role Of Ca 2+ In Dadsmentioning
confidence: 99%
“…Calcium handling, a term defines as entire process of Ca 2+ entry, store, release and reuptake, is central to the control of heart rhythm and contraction (Gwathmey et al 1987). Thus, it is not surprising that abnormalities in calcium handling have been involved as key elements in many forms of heart disease like VT. A recent study also suggested that irregular calcium handling may induce VT in canines with tachycardia-induced CHF (Hoeker et al 2009). Ca 2+ transport is governed by the"Ca 2+ container" inside heart cells, called sarcoplasmic reticulum (SR) (Levine and Loewen 2006).…”
mentioning
confidence: 99%